Epizootiological-Epidemiological Characteristics of the Stationary Hazardous as regards Anthrax Areas in the Stavropol Territory and North Caucasian Federal District - N. P. Buravtseva; V. M. Mezentsev; A. G. Ryazanova; S. N. Antyuganov; E. I. Eremenko; T. M. Golovinskaya; O. I. Tsygankova; N. G. Varfolomeeva; L. Yu. Aksenova (Проблемы особо опасных инфекций, 2016)
Objective of the study is to analyze epizootiological-epidemiological characteristics of the stationary hazardous as regards anthrax areas (SHA), situated in the territory of the North Caucasian Federal District (NCFD). Materials and methods. Official statistical data on morbidity rates in the Russian Federation and the records of the Rospotrebnadzor Administrations and Veterinary Administrations in the Stavropol Territory and the Republics of NCFD have been deployed for evaluation of anthrax incidence rates among humans and animals. Electronic cadastre for geo-encoding of SHA has been developed using software product ESRI (ArcGIS10.x) and topographical framework in the form of electronic maps M 1:200000. Results and conclusions. The studies conducted for the assessment of SHAs formation timelines and their activity during 1960-2014 have revealed that most of the SHAs fall under the category of the old-aged and non-manifesting ones. The highest peak of anthrax activity came in the period of 1960-1979. Further on, anthrax was registered within 1-3 years in scattered regions.